Photogrammetrics and clinical features of nasal siliconoma in Asians (Medical Journal of Indonesia, 2023)
BACKGROUND Nasal silicone injections have been a common procedure among Asians. However, this procedure can lead to severe complications. Unfortunately, there are limited data available on the distortive characteristics of nasal siliconoma in the Asian population. This study aimed to provide objective data on the distortive characteristics of nasal siliconoma to be a reference for a treatment outcome. METHODS This cross-sectional study was conducted at Cipto Mangunkusumo Hospital from June 2017 to March 2018. The study included 30 Asian females with nasal siliconoma, and nasal photogrammetric measurements were taken using a portable mirror stand device and analyzed to formulate the distortive characteristics. RESULTS The mean (standard deviation) of intercanthal width was 3.33 (0.25) cm, nasal root width was 2.70 (0.30) cm, alar width was 4.48 (0.31) cm, two tip-defining points (TDP) distance was 2.09 (0.22) cm, nasofrontal angle was 141.10 (8.40)°, length of the nose was 3.10 (0.48) cm, nasofacial angle was 32.94 (4.51)°, nasion projection was 0.64 (0.36) cm, pronasion projection was 2.00 (0.25–2.46) cm, tip angle was 122.7 (4.52)°, nasolabial angle was 78.81 (15.93)°, columella length (n = 20) was 0.64 (0.20) cm, tip lobular portion length was 1.12 (0.20) cm, the extend of extended columella was 0.47 (0.31) cm, and base of the nasal width was 3.98 (0.25) cm. CONCLUSIONS Nasal siliconoma in Asians had certain characteristics such as a wider nasal root, wider two TDP distance, wider nasion projection, acute nasolabial angle, hanging columella, and a long lobular portion of the tip.